Driving workplace sustainability: A literature review of employee behavior and participation in green office initiatives - Mohammad , Azlyantiny; Mohd Nasir, Nur Syazana; Muhamad, Marlina (International Journal of Accounting, Finance and Business, 2025)
Organizations across the globe adopt green office initiatives to minimize environmental impact because of sustainability trends. The variable field of employee engagement hinders the success of green office initiatives. Employee engagement within workplace sustainability programs constitutes the primary purpose of this study while it studies organizational barriers to sustainable behavior promotion together with environmental impact analysis and sustainability initiatives evaluation as well as Green Human Resource Management practice evaluation and pro-environmental behavioral patterns. By employing an SLR methodology the study examines peer-reviewed literature retrieved from Scopus AI and Web of Science and Google Scholar platforms for knowledge synthesis on this subject. Employee participation in green office initiatives shows strong dependence on organizational sustainability policies together with leadership commitment and GHRM practices. The sustainability efforts face obstacles from employee resistance to change and work-related priorities and limited motivational incentives. The research adds new value to organizational sustainability studies by uniting mandatory and voluntary environmental conduct and delivering applied solutions for workplace sustainability improvement. Organizations need to establish detailed sustainability standards while establishing HRM practices that serve environmental objectives together with developing green leadership environments to increase workforce engagement. Organizations should consider introducing both financial resources and non-economic motives to boost employee participation in their sustainability programs. Programs to keep employees involved in environmental initiatives require further study by examining time-based research across various business sectors and cultures for generating improved approaches. The research offers directions which organizations need to integrate sustainability into their workplace systems in combination with improved environmental results during the long term.